Forensic criminology - Williams, Andy (Routledge/Taylor & Francis Group, 2015)
This text provides an examination of the aetiological development of forensic criminology within the UK. It links the subjects of scientific criminology, criminal investigations, crime scene investigation, forensic science and the legal system, and provides an introduction to the important processes that take place from crime scene to courtroom.